The APISS questionnaire - Carli, Tanja (Zdravstveno varstvo, 2023)
Aim: To develop and validate a comprehensive questionnaire to be used as an instrument in cross-sectional studies among beekeepers. Methods: A comprehensive questionnaire in Slovenian was validated by an expert panel (n=13) for content relevance and a rater panel (n=14) for clarity and comprehensibility. The content validity indices (an item-level content validity index and scale-level content validity index based on the average and universal agreement method) and item-level face validity index were calculated in accordance with the recommended number of both the review panels with their implications on the acceptable cut-off scores. Piloting was performed in a sample (n=50) of the target population (N=1.080) using telephone interviews. Results: The item-level content validity index and scale-level content validity index based on the average method exhibited excellent content validity (0.97), while the scale-level content validity index based on the universal agreement method reached a value of 0.72. The item-level face validity index of 1.00 indicated that all items were clear and comprehensive. Conclusions: The new instrument may be considered valid and feasible for use in nationwide population-based studies among Slovenian beekeepers and eventually in other populations.
Keywords: beekeeping; čebelarjenje; hymenoptera; hypersensitivity; kožekrilci; preobčutljivost; questionnaire; vprašalniki